Lipid Transformations in Greening and Senescing Leaf Tissue - Newman, D. W. (1973)
Analyses were made of chlorophyll a and b and fatty acids (18:3, 18:2, 18:1, 18:0, 16:2, 16:1, and 16:0) of greening and senescing leaf tissue. Those dark-grown tissues given a prior treatment of red, far red, or red followed by far red light showed similar increases in chlorophylls and linolenate (18:3) when exposed to continuous white light. In contrast, green barley (Hordeum vulgare L.) leaves placed in the dark lost chlorophylls and fatty acids, especially 18:3. Senescing cocklebur (Xanthium strumarium L.) leaf tissue showed a decline in chlorophyll and fatty acids, especially again 18:3. Abscisic acid, but not sucrose, accelerated these senescent changes. Radioactive acetate incorporation into the galacto-lipids and phospholipids of senescing cocklebur leaf tissue increased and then the radioactivity of the lipids decreased in senescent tissues.